2021
DOI: 10.1038/s41598-020-80035-4
|View full text |Cite
|
Sign up to set email alerts
|

Lipid droplet biogenesis and COX-2 pathway activation are triggered by Barrett’s esophagus and adenocarcinoma, but not esophageal squamous cell carcinoma risk factors

Abstract: Esophageal cancer (EC) is an aggressive disease, presenting two main histological subtypes: adenocarcinoma (EAC) and squamous cell carcinoma (ESCC). The two EC subtypes widely differ concerning virtually all factors. ESCC development is mainly associated with tobacco and alcohol abuse, whereas obesity and chronic gastroesophageal reflux disease (GERD) are important risk factors not only for EAC, but also for for Barrett’s esophagus (BE), an intestinal metaplasia that precedes EAC. Obesity triggers ectopic lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…In the following, the most promising candidate gene per locus is highlighted: LDAH at 2p24 plays a role in tumour suppression and proliferation 49. The corresponding protein localises to lipid droplets and increased levels of lipid droplets have been found in EA versus BE and BE versus normal tissue 50 . RSRC1 at 3p25 is involved in mRNA splicing and may suppress gastric cancer cell proliferation 51 .…”
Section: Discussionmentioning
confidence: 99%
“…In the following, the most promising candidate gene per locus is highlighted: LDAH at 2p24 plays a role in tumour suppression and proliferation 49. The corresponding protein localises to lipid droplets and increased levels of lipid droplets have been found in EA versus BE and BE versus normal tissue 50 . RSRC1 at 3p25 is involved in mRNA splicing and may suppress gastric cancer cell proliferation 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies in different cell types, such as epithelial cells (IEC-6, CACO-2, and EAC cells) and macrophages infected with Mycobacterium bovis bacillus Calmette-Guerin (BCG), showed that LDs co-localize with COX-2 [ 69 ]. Importantly, this colocalization has been associated with increased prostaglandin E 2 levels at the sites where LDs were localized [ 70 , 71 , 72 , 73 , 74 ].…”
Section: Lipid Droplet Metabolismmentioning
confidence: 99%
“…According to the experimental studies of Carrossini et al, in BE and EAC, associated inflammatory stimulation would lead to a gradual increase in LD and a significant increase in IL-8 secretion. is phenomenon reveals an interaction between lipid droplets and inflammatory mediators, thus facilitating BE and EAC's occurrence and development [49]. Moreover, exogenous lipids could disrupt this metabolic program and have a negative effect on their effector function and ability to respond to stimuli, especially in the case of obesity [192][193][194].…”
Section: Esophageal Cancer Lipid Metabolism On Nk Cell In Thementioning
confidence: 99%
“…As demonstrated by recent investigations, the interaction of DGAT2 and MGAT2 can lead to the biosynthesis of lipid substrates for TGs [ 130 ]. According to Carrossini et al, LD increased with EAC evolution, which arose from the exposure of the esophageal epithelium to the hazard factors correlated with BE and EAC [ 49 ].…”
Section: Introduction To Esophageal Cancermentioning
confidence: 99%